Edukasi Penggunaan Moda Transportasi yang Aman Bagi Pelajar SMK Purnama 01 Semarang - Yesina Intan Pratiwi; Wardana Galih Pamungkas; Son Haji (Faculty of Engineering, Universitas Semarang, 2025)
This community service activity aims to educate students of SMK Purnama 01 Semarang about safe transportation options, focusing on reducing the risk of traffic accidents involving students. The main issue is the high number of accidents involving students using private vehicles and their limited understanding of traffic safety. The objective of this activity is to raise students' awareness of the importance of choosing safe transportation modes and applying the principles of